La fuerza muscular en adultos con insuficiencia renal y su influencia en la masa muscular. - Barzallo Pulupa, Yadira Nataly (2023)
This research analyze the incidence of physical activity and its benefits in people with renal insufficiency specifically in the process of hemodialysis, in addition, we investigated how muscle strength and muscle mass can increase by doing exercise by patients from a clinic called "Vida" which is located in the Chimborazo province in the city of Riobamba, the process was carried out through a twelve-week planning that consisted of a intervention of a physical exercises program aimed at strengthening lower limbs in those patients. We started this process by applying the test called "30 second sit to stand", in addition, a tape measure was used to take measurements of the thigh and calf, the pre and post intervention was carried out properly, our sample consisted of five male patients and five female patients, in short, ten patients in total. Once we have gotten all the information needed and the pre-test was applied, the exercises were carried out with a duration of twelve weeks, working two days a week and one hour a day so in that way we didn't change patients' routine drastically. It is also important to mention that the patients performed the exercises before they start the dialysis process. Once the twelve weeks of intervention with exercises were finished, the measurements of both the thigh and calf were taken again, at the same time the post-intervention was carried out using the "30 seconds sit to stand test" once again in order to demonstrate if there was actually an increase in strength in the lower extremities of the patients and if these kind of exercises really helped to increase muscle mass, as results we obtained an increase in muscle strength as well as muscle mass increased a little in these patients. We can conclude by mentioning that the implementation of the physical exercises program itself was beneficial for the patients since they not only gained muscle strength but also muscle mass, therefore we can say that at least in ten patients of the clinic called "Vida" the application of our research was successful.